Assessing the magmatic affinity and petrogenesis of granitoids at the giant Aktogai porphyry Cu deposit, central Kazakhstan - Cao, M.; Li, G.; Qin, K.; Evans, Noreen; Seitmuratova, E. (American Journal of Science, 2016)
Most mineralized porphyries associated with large to giant oxidized porphyry Cu deposits show an affinity with high Sr/Y rocks, while barren or weakly mineralized granitoids show typical low Sr/Y features. The Aktogai giant porphyry Cu deposit occurs in the Koldar pluton and provides a good natural laboratory in which to investigate this relationship, while determining the petrogenesis of the pluton and its mineralization. Zircon U-Pb dating, mineral chemistry, whole rock geochemistry and Sr-Nd-Pb and zircon Hf-O isotopic analyses were carried out on the pre-ore granodiorite (the major component of the Koldar pluton) and on the mineralized granodiorite porphyry. Zircon U-Pb ages indicate that the pre-ore granodiorite and mineralized granodiorite porphyries were emplaced at 345 and 328 to 331 Ma, respectively. Distinctly higher apatite SO3 contents in the granodiorite porphyry relative to the granodiorite suggest an increase in fO2 during the petrogenesis of the mineralized porphyries (>NNO+1). Although all rocks share similar geochemical characteristics (calc-alkaline, strong depletion in Nb, Ta and Ti, and enrichment in LREE and LILE), the pre-ore Koldar pluton has normal arc related magmatic features [low Sr/Y and (La/Yb)N, high Y and YbN], while the granodiorite porphyries and diorite (trace component of Koldar pluton) exhibit high Sr/Y and (La/Yb)N, low Y and YbN features. All samples show similar Sr-Nd-Pb-Hf-O isotopic compositions [(87Sr/86Sr)i = 0.70369 to 0.70413, ?Nd (t) = + 3.6 to + 5.6, (206Pb/204Pb)i = 18.16 to 19.32, zircon ?Hf (t) = + 11.8 to + 15.9, and d18O = + 3.8 to + 5.9 %.], and very young whole rock T2DM (Nd) (640-680 Ma) and zircon TDMC (Hf) (320-590 Ma) values, suggesting that they were probably derived from partial melting of juvenile lower crust. Geochemical patterns and partial melt modeling indicate that the high Sr/Y rocks were probably formed by partial melting of eclogitized, thickened lower crust, while the Koldar pluton formed by partial melting of normal thick lower crust. We propose that pre-ore low Sr/Y rocks were probably generated earlier via subduction of Junggar-Balkhash oceanic crust, and that the high Sr/Y rocks were formed later by partial melting of sulfide-enriched, thickened juvenile lower crust. High oxygen fugacity and the high melting temperature of the high Sr/Y rocks ensured that all sulfide was dissolved in the magma, which intruded the previously emplaced low Sr/Y pluton and resulted in significant mineralization.